1994
DOI: 10.1164/ajrccm.150.2.8049845
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of reversibility of airflow obstruction.

Abstract: The application of the forced oscillation technique to assess reversibility of airflow obstruction was compared with that of indices of forced expiration and plethysmographic airway resistance (Raw). In 125 patients with airflow obstruction, we measured total respiratory resistance (Rrs) and reactance (Xrs), Raw and specific airway conductance (sGaw), maximal flow-volume curves and forced expiratory volume in 1 s (FEV1), before and 30 min after 2 x 20 micrograms salbutamol by MDI. Salbutamol induced significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
5

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 0 publications
10
78
5
Order By: Relevance
“…Previous studies assessing bronchodilatation have shown that the greatest percentage change is observed using sGaw, leading to the conclusion that this is the most sensitive method [13][14][15][16]. However, these studies have limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies assessing bronchodilatation have shown that the greatest percentage change is observed using sGaw, leading to the conclusion that this is the most sensitive method [13][14][15][16]. However, these studies have limitations.…”
Section: Discussionmentioning
confidence: 99%
“…First, variability has not always been taken into consideration when assessing the physiological changes caused by a drug [14,15]. Second, the majority of the studies have only used one drug dose (usually a standard clinical dose) [13][14][15]. Consequently, the utility of spirometry, plethysmography and IOS to detect small changes while taking into account method variation, which is critical when assessing the full dose-response curve, is not known.…”
Section: Discussionmentioning
confidence: 99%
“…We used the sensitive pulmonary function measurement of specific airway conductance as the primary end point to compare the different treatment regimens. [18][19][20][21] Pulmonary function measurements of spirometry and lung volumes were also performed, and symptom scores were evaluated.…”
mentioning
confidence: 99%
“…11 Additionally, during plethysmography 'responders' achieved an improvement in sGaw equal to or greater than 40%. 17 Those with less than these thresholds were classified as 'nonresponders'.…”
Section: Methodsmentioning
confidence: 99%
“…Secondarily, we hoped to clarify the effect of baclofen on the airway tone of these subjects. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], studied during the same time period. All participants were screened for a history of pulmonary disease or respiratory symptoms, recent respiratory viral or bacterial infection, and asthma or seasonal allergy.…”
Section: Associated With Cervical Spinal Cord Injury (Sci)mentioning
confidence: 99%